2016
DOI: 10.1002/chem.201600048
|View full text |Cite
|
Sign up to set email alerts
|

Formation and High Reactivity of the anti‐Dioxo Form of High‐Spin μ‐Oxodioxodiiron(IV) as the Active Species That Cleaves Strong C−H Bonds

Abstract: Recently, it was shown that μ‐oxo‐μ‐peroxodiiron(III) is converted to high‐spin μ‐oxodioxodiiron(IV) through O−O bond scission. Herein, the formation and high reactivity of the anti‐dioxo form of high‐spin μ‐oxodioxodiiron(IV) as the active oxidant are demonstrated on the basis of resonance Raman and electronic‐absorption spectral changes, detailed kinetic studies, DFT calculations, activation parameters, kinetic isotope effects (KIE), and catalytic oxidation of alkanes. Decay of μ‐oxodioxodiiron(IV) was great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…220,232 At lower temperatures, however, it is possible to see the formation of visible chromophores suggestive of the formation of ( μ -1,2-peroxo)diferric species, as discussed in section 4.1. 192,219,220…”
Section: Models For Reaction Intermediates Of Diiron Enzymesmentioning
confidence: 99%
“…220,232 At lower temperatures, however, it is possible to see the formation of visible chromophores suggestive of the formation of ( μ -1,2-peroxo)diferric species, as discussed in section 4.1. 192,219,220…”
Section: Models For Reaction Intermediates Of Diiron Enzymesmentioning
confidence: 99%
“…A fourth example (along the blue path in Scheme 6) describes the reaction of [Fe III 2 (μ-O)(6-HPA)(OH 2 ) 2 ] 4+ (6-HPA = 1,2-bis{2-[bis(2-pyridylmethyl)aminomethyl]pyridin-6-yl}-ethane) with H 2 O 2 and 2 equiv of Et 3 N to generate a (μ-oxo)(μ-1,2-peroxo)diiron(III) derivative that is in equilibrium with a diiron(IV) intermediate with an OFe IV −O−Fe IV O core. 53,54 In contrast, the formation of high-valent 3 from 2 (along the red path in Scheme 6) occurs by introducing Sc 3+ (and not a proton), representing the first instance of a Lewis acidmediated O−O bond cleavage in a diiron system. In fact, adding a Brønsted acid like HClO 4 or HOTf to 2 results in the protonation of its oxo bridge to form 2 + H + .…”
Section: ■ Summary and Perspectivesmentioning
confidence: 99%
“…This process is a reverse process of oxygen activation reported by both Que [15h] and Kodera [15f] . In O 2 activation, Kodera suggested that a syn ‐dioxo form of catalyst 2 was transformed into anti ‐dioxo form through a t ‐oxo‐di(μ‐oxo)diiron(IV) transition state [15f,j] …”
Section: Resultsmentioning
confidence: 80%